2011
DOI: 10.4067/s0718-58392011000300017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sugars and Organic Acids in Commercial Varieties of Table Grapes

Abstract: Flavor composition has been defined as a complex attribute of fruit quality, in which the mix of sugars, acids and volatiles play a primary role. In table grapes (Vitis vinifera L.), sweetness and sourness are the most important flavor attributes for fresh consumption. However, most of the studies available have been performed on wine grapes, which are grown, cultured and processed differently to table grapes. Therefore, the objective of this work was to characterize the changes in sugars and organic acids dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 21 publications
5
55
0
1
Order By: Relevance
“…Williams et al [17] found an increase in berry sugar with water application under 60% of ETc in Thompson Seedless for raisins. However, juice acidity was between 0.7 and 0.8 mg of tartaric acid/100 mL juice in all years and treatments; these are considered normal values for this variety [33]. Also, shattering was very low (less than 1.7%) in all treatments and all years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Williams et al [17] found an increase in berry sugar with water application under 60% of ETc in Thompson Seedless for raisins. However, juice acidity was between 0.7 and 0.8 mg of tartaric acid/100 mL juice in all years and treatments; these are considered normal values for this variety [33]. Also, shattering was very low (less than 1.7%) in all treatments and all years.…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with the results of Selles et al [32], who found that with less than 80% ISR there was a predominance of yellow color in this cultivar. The quality parameters firmness (Table 6) and sugar content (Table 7) were not affected by the irrigation treatment in any experimental year, and were in the normal range for this cultivar [33]. Williams et al [17] found an increase in berry sugar with water application under 60% of ETc in Thompson Seedless for raisins.…”
Section: Resultsmentioning
confidence: 99%
“…acidity and soluble sugars are important parameters for blackberries market and can serve as a reference to classify fruit pulp for juice production. the ratio between sugars and organic acids has been linked as a parameter of flavor quality between cultivars, and can also be used as a harvest parameter (MUñOz-ROBREDO et al, (2011). conclusions blackberries produced under the conditions of Western paraná contain high levels of antioxidants, with emphasis on arapaho cultivar.…”
Section: Wrolstad 2005)mentioning
confidence: 99%
“…total soluble solids content was determined in a benchtop refractometer (Quimis QI-107.1), and expressed in °Brix, and total titratable acidity was determined by titration with sodium hydroxide (NaOH 0.1 mol L -1 ) and phenolphthalein 1% as an indicator, with results expressed in g 100 g -1 of fresh weight in citric acid equivalent (MUñoz-ROBREDO et al, 2011). Ascorbic acid content was determined by titration with 2,6-dichlorophenolindophenol and the results expressed in mg 100 g -1 of fresh weight.…”
Section: Soluble Solids Titratable Acidity Ph and Ascorbic Acidmentioning
confidence: 99%
“…These indexes are influenced by the nature and source of carbohydrates and organic acids present in beverages and may be calculated from their contents, usually obtained experimentally by liquid chromatography based techniques [15][16][17][18]. These approaches, although accurate, are time-consuming, expensive, require qualified technical human resources and, usually, are not ambient friendly.…”
Section: Introductionmentioning
confidence: 99%